Tracking and Trading: Expanding on Options for International Greenhouse Gas Unit Accounting after 2012 - Prag, Andrew (OECD/IEA Climate Change Expert Group Papers, 2011)
The use of tradable greenhouse gas (GHG) units to meet emissions reduction goals is likely to continue after 2012 as many countries have expressed support for using market mechanisms to promote and enhance the cost-effectiveness of mitigation. Most such mechanisms would use tradable GHG units but it is not yet clear how such units will be accounted for and recognised as contributions toward national pledges or targets. This paper examines the systems and processes that may be required to achieve effective use of tradable GHG units by first considering what international framework would be required to provide a reliable, functional platform for use of tradable GHG units. One effective system would be for national emissions to be reported using common inventory accounting rules, with subsequent additions and deductions according to net flows of tradable units.